Ad hoc solid electrolyte on acidized carbon nanotube paper improves cycle life of lithium–sulfur batteries. Issue 12 (27th September 2017) - Xu, Guiyin; Kushima, Akihiro; Yuan, Jiaren; Dou, Hui; Xue, Weijiang; Zhang, Xiaogang; Yan, Xiaohong; Li, Ju
Abstract : The in situ polymerized solid barrier stops sulfur transport while still allowing bidirectional Li + transport, alleviating the shuttle effect and increasing the cycling performance. Abstract : The performance of lithium–sulfur (Li–S) batteries is greatly improved by using acidized carbon nanotube paper (ACNTP) to induce in situ polymerization of ether-based DOL/DME liquid to grow an ion-selective solid barrier, to seal in soluble polysulfides on the cathode side. The Li–S battery with the in situ barrier showed an initial specific capacity of 683 mA h g −1 at a high current density of 1675 mA g −1, and maintained a discharge capacity of 454 mA h g −1 after 400 cycles. The capacity decay rate was 0.1% per cycle and a high Coulombic efficiency of 99% was achieved. Experimental characterizations and theoretical models demonstrate the in situ polymerized solid barrier stops sulfur transport while still allowing bidirectional Li + transport, alleviating the shuttle effect and increasing the cycling performance. The soft and sticky nature of the solid electrolyte barrier makes it a good sealant, forming an enclosed catholyte chamber on the sulfur side.